Innovation activity - a factor for increasing competitiveness - Adriana Atanasova (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2024)
As globalisation processes evolve, there is increasing "pressure" and need for companies to enhance their innovation activity. The development and integration of an innovation strategy, taking into account all the chances and risks, in a new knowledge-based economic environment and dynamic market conditions, determines the scientific and practical interest in innovations capable of ensuring successful competitiveness Competitiveness stems from building capabilities necessary to sustain growth in a regional, national and international competitive environment. Such capabilities are created primarily through innovation and its deployment, allowing multiple potential pathways to success.
Keywords: O30; O31; O33; 330; Innovations; innovation activity; innovation environment; competitiveness; knowledge economy; competitiveness